The Aztecs under Spanish rule a history of the Indians of the Valley of Mexico : 1519-1810 - Gibson, Charles (Stanford University Press, 1964)
Outlines the influence that Spanish rule had upon all aspects of Aztec life during the three hundred years after their conquest.
Keywords: Geschichte 1519-1810; Aztèques; Aztèques, 1519-1810; Colonisation espagnole, Mexique, 1519-1810; Espagne - Colonies - Administration; Espagne, Colonie, Mexique, 1519-1810; Indianen; Indiens - Mexique; Indiens d'Amérique - Mexique - Mexico, Vallée de; Koloniaal bestuur; Mexique - Jusqu'à 1810; Mexique, 1519-1810; Geschichte; Indianer; Kolonie; Indians of Mexico -- Mexico -- Mexico, Valley of; Azteken; Espagne - Colonies - Amérique - Administration; Mexique - Histoire - Jusqu'à 1810; Mexiko; Spanien; Mexico -- History -- To 1810; Spain -- Colonies -- Administration